Educational Games of Introducing English to Early Childhood - Gunawan, Rico Ferdian; Chandrawati, T. Brenda; Prasetya, FX. Hendra (Soegijapranata Catholic University, 2024)
In early childhood, they usually begin exploring many things, such as learning, playing and imitating the behaviour of older people. Children learn to communicate with others and from their peers at a certain age. Children also learn to recognize letters of the alphabet, self-recognition and surrounding objects. The following year, children recognize other languages, such as English. Then, year by year, children start learning many languages, such as English. This educational game will be for English furniture for children. When children play games, they are usually accompanied by parents to guide and teach them to play games. The educational game